2021
DOI: 10.1111/bju.15421
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted Boari flap and psoas hitch ureteric reimplantation: technique insight and outcomes of a case series with ≥1 year of follow‐up

Abstract: ObjectiveTo describe step-by-step surgical techniques and report outcomes of the largest single-centre series of patients with distal ureteric disease exclusively treated with robot-assisted ureteric reimplantation with Boari flap (RABFUR) and psoas hitch (RAPHUR), with a minimum follow-up of 1 year and complete postoperative data. Patients and MethodsA total of 37 patients with distal ureteric disease were treated between 2010 and 2018. Of these, 81% and 19% underwent RAPHUR and RABFUR, respectively. Intra-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Fugita OE et al (5)performed the first successful laparoscopic Boari flap in three patients with long-segment ureteral stricture in 2001 and confirmed that the procedure was effective and feasible.Ding G et al (20)retrospectively reviewed 35 patients with complex distal ureteral stricture.compared to open Boari flap-psoas hitch,laparoscopic surgery had advantages being a minimal invasive surgery with less estimated blood loss and fewer surgical complications.We summarize some of the teams that performed Boari flap in the laparoscopic approach,as shown in Table 3 (9,(21)(22)(23)(24)(25)(26)(27).In our study,perioperative outcomes were similar to them.During long-term follow-up,one patient developed ureteral stricture and severe hydronephrosis one year after surgery,and hydronephrosis was reduced after placement of 2 double J-tubes,and one patient had recurrent urinary tract infection,while the remaining fifteen cases did not show any abnormalities.Damage to the blood supply to the bladder flap during surgery,operator's unskilled suturing technique,the patient's own nutritional status,and poor control of diabetes mellitus may have been associated with ureteral stenosis in this patient.In recent years,robot-assisted Boari flap has been reported,and its efficacy and safety have been confirmed (28,29).However,its high price is prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…Fugita OE et al (5)performed the first successful laparoscopic Boari flap in three patients with long-segment ureteral stricture in 2001 and confirmed that the procedure was effective and feasible.Ding G et al (20)retrospectively reviewed 35 patients with complex distal ureteral stricture.compared to open Boari flap-psoas hitch,laparoscopic surgery had advantages being a minimal invasive surgery with less estimated blood loss and fewer surgical complications.We summarize some of the teams that performed Boari flap in the laparoscopic approach,as shown in Table 3 (9,(21)(22)(23)(24)(25)(26)(27).In our study,perioperative outcomes were similar to them.During long-term follow-up,one patient developed ureteral stricture and severe hydronephrosis one year after surgery,and hydronephrosis was reduced after placement of 2 double J-tubes,and one patient had recurrent urinary tract infection,while the remaining fifteen cases did not show any abnormalities.Damage to the blood supply to the bladder flap during surgery,operator's unskilled suturing technique,the patient's own nutritional status,and poor control of diabetes mellitus may have been associated with ureteral stenosis in this patient.In recent years,robot-assisted Boari flap has been reported,and its efficacy and safety have been confirmed (28,29).However,its high price is prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, at a time when the da Vinci SP platform is not available in Europe, our results showed that Xi r-RPP represents a safe alternative to standard RARP. Moreover, we reported the complications of r-RPP according to European Association of Urology “ad hoc” panel guidelines for the first time, which allow to increase the accuracy of the analysis and avoid missing complication reporting [24] , [25] , [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the identical invasiveness and cosmetic outcomes of LESS, after accumulating enough laparoscopic experience [ 20 , 21 , 22 ], we have tried and successfully performed many TMLUR surgeries by using the usual instruments in children, which has not been previously reported in the published literature. Recently, numbers of RALUR have increased annually and progressively overshadow conventional LUR due to its instinct technical advantages [ 4 , 9 , 10 , 11 , 12 , 23 ]. Meanwhile, since urologists in our center are proficient in robot-assisted laparoscopic skills, since 2019 RALUR is applied for DUS in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…By offering specialized technical advantages such as high-resolution three-dimensional view, tremor filtration with motion scaling and highly dexterous wrist-like instruments [ 4 , 9 , 10 ], the robotic surgical system dramatically improves laparoscopy by providing finer movement and easier intracorporeal suturing. Thus, robot assisted LUR (RALUR) is gradually substituting for conventional LUR as the first option for UR and achieved satisfactory results during the last decade in many high-volume centers [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%